POLA PENYEBARAN DAN REGENERASI JENIS SANINTEN (Castanopsis argentea Blume) DI RESORT SELABINTANA, TAMAN NASIONAL GUNUNG GEDE PANGRANGO Distribution Pattern and Regeneration of Saninten (Castanopsis argantea Blume) in Selabintana Resort, Gunung Gede - Iwan Hilwan; Ewi Irfani (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2018)
Saninten (Castanopsis argantea Blume) known as one of Indonesian indigenous tree species that has high value. Saninten found at Gunung Gede Pangrango National Park especially Resort Selabintana. Saninten produce fruits that can be consumed and wood that can be used as building materials. Regarding these facts, this tree species needs to be cultivated. The distribution pattern of saninten is needed for the right development, but the study about ecology andnatural population of this species is rare and less known. The aim of this research was to asses potential, regeneration and the distribution pattern of saninten. The research used a combination of lanes and line method with counturs cutting. The result showed that distribution of saninten in both location is clumped. Morishita index in lower attitude was 1.68 and in upper attitude was 1.29.Key words: C. argentea, distribution, Resort Selabintana, Taman Nasional Gunung Gede Pangrango